RESPON PERILAKU TERHADAP PERUBAHAN MODEL ANGGARAN DAN LAPORAN KEUANGAN UNTUK PENINGKATAN AKUNTABILITAS PUBLIK LEMBAGA PENDIDIKAN - Hermawan, Sigit (Journal of Innovation in Business and Economics, 2011)
This article reviewed the response and behavior of the change-related budgets model  and financial reports in an effort to improve accountablityin public institution. This article is based on research conducted  2004 to 2009 in an institution of education. The results of the study concluded  the response informant key to approve the proposed changes, although there is a statement which agrees with the notes. While the behavior associated with policies  can improve the public accountability of education institutions,the question is whether we should  take a policy of top-down or bottom-up.